Preliminary investigations on the parasite burden and distribution of endoparasite species of muskox (Ovibos moschatus) and caribou (Rangifer tarandus groenlandicus) in West Greenland - Korsholm, H.; Olesen, C. R. (Rangifer, 1993)
In the autumn 1990 5 muskoxen and 5 caribou from Angujaartorpfiup Nunaa, West Greenland, were parasitologically examined. The findings included gastro-intestinal parasites as Eimeria spp., Ostertagia cir-cumcincta, Ostertagia trifurcata, Teladorsagia davtianiy Marshallagia marshalli, Nematodirella longissimespiculata, Nematodirus helvetianus and Moniezia expansa. No pulmonic or hepatic parasites were detected. A theoretically possible interaction of parasite species between muskox and caribou is most likely in the case of Ostertagia spp. and N. longissimespiculata. Preliminary investigations on the contamination of infective larvae (third stage larvae of gastro-intestinal nematodes) showed great differences on herbage from different types of habitats in the research area. A moist dwarf schrub heat on a north facing slope being the most contaminated (1643 L3/kg of dry herbage).